Efficacy, Retention, and Tolerability of Brivaracetam in Patients With Epileptic Encephalopathies: A Multicenter Cohort Study From Germany - Willems, Laurent M.; Bertsche, Astrid; Bösebeck, Frank; Hornemann, Frauke; Immisch, Ilka; Klein, Karl M.; Knake, Susanne; Kunz, Rhina; Kurlemann, Gerhard; Langenbruch, Lisa; Möddel, Gabriel; Müller-Schlüter, Karen; et al. (Frontiers in Neurology, 2018)
Objective: To evaluate the efficacy and tolerability of brivaracetam (BRV) in a severely drug refractory cohort of patients with epileptic encephalopathies (EE). Method: A multicenter, retrospective cohort study recruiting all patients treated with EE who began treatment with BRV in an enrolling epilepsy center between 2016 and 2017. Results: Forty-four patients (27 male [61%], mean age 29 years, range 6 to 62) were treated with BRV. The retention rate was 65% at three months, 52% at 6 months and 41% at 12 months. A mean retention time of 5 months resulted in a cumulative exposure to BRV of 310 months. Three patients were seizure free during the baseline. At three months, 20 (45%, 20/44 as per intention-to-treat analysis considering all patients that started BRV including three who were seizure free during baseline) were either seizure free (n=4; 9%, three of them already seizure-free at baseline) or reported at least 25% (n=4; 9%) or 50% (n=12; 27%) reduction in seizures. There was no change in the frequency of seizures in ten patients (23%), an increase in seizure frequency was reported in two (5%) patients. At the six months follow-up, 45% of the patients (n=20) had a 50% response or were seizure free (n=2, 5%). Treatment-emergent adverse events were predominantly of psycho-behavioural nature and were observed in 16%. Significance: In this retrospective analysis the rate of patients with a 50% seizure reduction under BRV proofed to be similar to those seen in regulatory trials for focal epilepsies. BRV appears to be safe and relatively well tolerated in EE and might be considered in patients with psychobehavioral adverse events while on levetiracetam.